2010
DOI: 10.3168/jds.2009-2823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous milking during the dry period or once daily milking in the first 4 weeks of lactation on metabolism and productivity of dairy cows

Abstract: The objective was to compare the effects of 3 management systems in high-yielding dairy cows on metabolic profiles and milk production. Thirty-six multiparous Brown Swiss cows were randomly assigned to 1 of 3 treatment groups (n=12 cows/group): the control (C) group, in which cows were dried off 56 d before calving and milked twice daily throughout next lactation (305 d); the once daily milking (ODM) group, in which cows were dried off 56 d before calving and milked once daily for the first 4 wk of lactation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 58 publications
(96 reference statements)
14
74
1
2
Order By: Relevance
“…In the literature slightly higher percentages are stated: Losses between 16.5% and 22% are measured in similar trials (Remond et al, 1997a and1997b;Andersen et al, 2005;Schlamberger et al, 2010). In contrast to that, as described by Remond et al (1997a), the milk quantity of the D group was not even then achieved by continuously milked cows, if the milk produced during the continuous milking period was added to the 305-day yield.…”
Section: Fertilitymentioning
confidence: 86%
See 2 more Smart Citations
“…In the literature slightly higher percentages are stated: Losses between 16.5% and 22% are measured in similar trials (Remond et al, 1997a and1997b;Andersen et al, 2005;Schlamberger et al, 2010). In contrast to that, as described by Remond et al (1997a), the milk quantity of the D group was not even then achieved by continuously milked cows, if the milk produced during the continuous milking period was added to the 305-day yield.…”
Section: Fertilitymentioning
confidence: 86%
“…Concerning the BHBA, NEFA, calcium, IGF-1 blood concentration and the changes of the back fat thickness, a clear interference of the milking regimen could be shown. An improvement of the metabolic condition is also assessed in other studies (Rastani et al, 2005;Schlamberger et al, 2010). Andersen et al (2005) proves in his trial by milking 14 HolsteinFriesian cows continuously that those cows show considerably lower BHBA and NEFA blood concentrations than the 14 cows of the test group with a 7-week drying-off period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that cows with short or omitted dry periods show improved dry matter intake, metabolic profiles, body condition score, BW and mean negative energy balance ( Pezeshki et al, 2007 andWatters et al, 2008). It appears that following short or eliminated dry periods, the energy balance is improved around calving by reduced milk production, less nutritional and metabolic stress and the resulting ease of transition to lactation (Pezeshki et al, 2007 andSchlamberger et al, 2010).…”
Section: Altered Dry Periodsmentioning
confidence: 99%
“…Milk yield loss as a result of dry period reduction was reported to be stronger for primiparous cows than for multiparous cows (Annen et al, 2004, Pezeshki et al, 2007. Cows without a dry period were reported to produce approximately 800 -1200 kg milk during the last 56 -60 days of lactation (Schlamberger et al, 2010, Annen et al, 2004. The total energy corrected milk yield over a whole lactation of continuously milked cows was 600 kg lower compared with cows with a 60 d dry period (Schlamberger et al, 2010).…”
Section: Energy Balance Milk Production and Compositionmentioning
confidence: 99%